UNMISSED FEMALE BABY IN THE QURâ€™AN: - Fathurrosyid, Fathurrosyid (State Institute of Islamic Studies (IAIN) Palu, 2018)
This research raises two main issues; First, what is a literary psychology? Second, how is the psychological construction of Maryam in the Qurâ€™an from the perspective of literary psychology? The method used is descriptive-analytical based on the theory of literary psychology. In the context of the story of Maryam, the study of psychology that is intended is the theory of psychoanalysis and complex psychology, especially extrovert and introvert types. This study concludes; First, literary psychology is a form of study and analysis based on the psychological point of view dealing with life events. Second, psychological construction of Maryam in the Qurâ€™an includes; (a) The psychology of convergence between empiricism and nativism. (b) Maryamâ€™s personality structure includes the id, ego and super ego narrated in Maryam [19]: 18, 20 and 22. (c) The personality typology of Maryam is an introvert figure. The indicator is in Maryam [19]: 26 who prefers the â€œeat and drinkâ€ commandment to the â€œbe happyâ€ commandment. The grammatical structure is to consider introvert typology oriented to emotional eating.